Mineralogy, Micro-fabric and the Behavior of the Completely Decomposed Granite Soils - Elsayed Elkamhawy; Bo Zhou; Huabin Wang (Civil Engineering Journal, 2019)
The main objective of this study is to investigate the impact of the micro-fabric and soil mineralogy on the overall macro-behavior of the completely decomposed granite soil through a set of drained and undrained triaxial shearing and isotropic compression tests on a medium-coarse grading completely decomposed granite soil. The mineral composition of the soil was a substantial factor governing the compressive behavior. The soil compressibility increased significantly in the case of existence crushable and weak minerals within the soil minerals like fragile feldspar, as well as the high content of fines, especially the plastic fines. The scanning electron microscopic photos indicated that the micro-fabric of the soil had a paramount impact on the compressive behavior. The mechanism of the volumetric change depended on the stress levels, the soil mineral composition and the grain morphology. In the low consolidated stress levels, the soils’ grains rearrangement was the prevailing mechanism of the volumetric change, particularly with the absence of weak and crushable minerals. On the other hand, at the high consolidated stress levels, particles’ crushing was the prevailing mechanism in the volumetric change. Both the mechanisms of volume change could occur simultaneously at the low stress levels in the case of presence crushable minerals in addition to micro-cracks in the soil grains. The soil showed an isotropic response after 250 kPa, as this stress level erased the induced anisotropy from the moist tamping preparation method. Under the drained shearing conditions, the soil showed a contractive response, while during the undrained shearing conditions, the soil exhibited both the contractive and dilative responses with phase transformation points. The studied soil showed a unique critical state line, irrespective of the drainage conditions and initial states, the critical state line was parallel to the isotropic compression line in the void ratio effective stress space. In the deviator effective mean stresses space, the studied soil approached a unique CSL with a critical stress ratio equal 1.5, corresponding to critical friction angle of 36.8°.